Vision-based traffic sign detection and recognition systems: Current trends and challenges - Wali S.B.; Abdullah M.A.; Hannan M.A.; Hussain A.; Samad S.A.; Ker P.J.; Mansor M.B. (MDPI AG, 2023)
Automobile drivers; Computer vision; Traffic signs; Comparative studies; Driver assistance system; Issues and challenges; Performance metrics; Research communities; Tracking and classification; Traffic sign detection; Traffic sign detection and recognition; Advanced driver assistance systems